Downregulation of microRNA‐107 in intestinal CD11c+ myeloid cells in response to microbiota and proinflammatory cytokines increases IL‐23p19 expression. (13th January 2014) - Xue, Xiaochang; Cao, Anthony T.; Cao, Xiaocang; Yao, Suxia; Carlsen, Eric D.; Soong, Lynn; Liu, Chang‐Gong; Liu, Xiuping; Liu, Zhanju; Duck, L. Wayne; Elson, Charles O.; Cong, Yingzi
<x xml:space="preserve">Abstract</x> Commensal flora plays an important role in the development of the mucosal immune system and in maintaining intestinal homeostasis. However, the mechanisms involved in regulation of host‐microbiota interaction are still not completely understood. In this study, we examined how microbiota and intestinal inflammatory conditions regulate host microRNA expression and observed lower microRNA‐107 (miR‐107) expression in the inflamed intestines of colitic mice, compared with that in normal control mice. miR‐107 was predominantly reduced in epithelial cells and CD11c+ myeloid cells including dendritic cells and macrophages in the inflamed intestines. We demonstrate that IL‐6, IFN‐γ, and TNF‐α downregulated, whereas TGF‐β promoted, miR‐107 expression. In addition, miR‐107 expression was higher in the intestines of germ‐free mice than in mice housed under specific pathogen‐free conditions, and the presence of microbiota downregulated miR‐107 expression in DCs and macrophages in a MyD88‐ and NF‐κB‐dependent manner. We determined that the ectopic expression of miR‐107 specifically repressed the expression of IL‐23p19, a key molecule in innate immune responses to commensal bacteria. We concluded that regulation of miR‐107 by intestinal microbiota and proinflammatory cytokine serve as an important pathway for maintaining intestinal homeostasis.